PENINGKATAN KEMAMPUAN SISWA TK AL AFSHAH BERKOMUNIKASI SECARA SEDERHANA DALAM BAHASA INGGRIS DENGAN COMMUNICATIVE LANGUAGE TEACHING - Wijirahayu, Suciana; Hasanudin, Dede (MAJALAH ILMIAH WIDYA, 2012)
Currently the introduction of English as a foreign language in kindergarten seems to have become so popular that the kindergarten teacher trying to teach it. The purpose of this study is generally to find out the success of improving the mastery of list of words and pronunciation especially in kindergarten with Learning Contextual method. The research used survey observation method which conducted at 30 kindergartens in Jakarta and Tanggerang area.The results obtained that after observing the students who have difficulties memorizing lists of words without realia in the cycle after the action I, the mean value of 53% verbal 4:33 students. Although there has been increased of 1.69 points (53%), but the acquisition has not been satisfactory.